View of the Paintings in the Oval Cartouches in the Ceiling - Temples of India Project Team (Jio Institute, 2024)
A closer view of the paintings in the oval cartouches in the ceiling of the mandapa (pillared hall) of the Bhandasar Temple. Seen here are five such ovals. The lower set has two paintings, one is the story of Jinadatta Suri subduing the five pairs of the five waters and the other is the story of Jinachandra Suri who converted the no moon day to a full moon day. The upper set has stories from the life of Mahavir Swami, the Tirthankara. The oval shapes of the paintings are designed like mirror frames. This style is influenced by European paintings, especially the Company style paintings produced during the 18th-19th centuries CE.